The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00380-018-1141-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of myocardial fibrosis in adults with Ebstein’s anomaly

Abstract: Heart failure and arrhythmia are common complications in adults with Ebstein’s anomaly. They may result not only from hemodynamic alterations, but also from myocardial fibrosis. Late gadolinium enhancement (LGE) by CMR enables the evaluation of myocardial fibrosis. The aim of the study was to asses the presence of LGE and its relation to clinical outcome. We studied a group of 37 unoperated adults aged 43.0 ± 14.4 years with Ebstein’s anomaly from the congenital heart disease outpatient clinic. Study protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…A study on 37 patients with ebstein anomaly in adulthood aged 43.0 ± 14.4 years revealed that fibrosis was the initial cause of arrhythmias and heart failure assessed by LGE on cardiac MRI. 20% of patients reaching adulthood died from arrhythmias, whereas 50% died from heart failure [9]. Sudden cardiac death may occur in asymptomatic patients with mild disease and normal cardiothoracic index on chest-X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 37 patients with ebstein anomaly in adulthood aged 43.0 ± 14.4 years revealed that fibrosis was the initial cause of arrhythmias and heart failure assessed by LGE on cardiac MRI. 20% of patients reaching adulthood died from arrhythmias, whereas 50% died from heart failure [9]. Sudden cardiac death may occur in asymptomatic patients with mild disease and normal cardiothoracic index on chest-X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Late gadolinium enhancement (LGE) in various CHD revealed important prognostic associations between solid myocardial fibrosis and adverse clinical outcomes (49)(50)(51). In adults with EA, LGE highlighting myocardial scar tissue was a frequent finding within the right atrium and right ventricle (52). However, LGE is less reliable for B A detecting diffuse fibrosis, which is common in CHD (53).…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…However, even when tricuspid valve repair is carried out early RV performance cannot be restored to a satisfactory level in some cases. Structural RV myocardial changes have been described in EA which may be accountable for reduced RV performance (12,14,52). In this context, the optimal timing for surgery remains unclear.…”
Section: Open Questions and Future Perspectivesmentioning
confidence: 99%
“…Further evaluation can be done with cardiac magnetic resonance imaging (MRI), which can provide better quantification of RV size and function [ 12 ]. Cardiac MRI is also useful in locating fibrosis (late gadolinium enhancement) which can be focal or diffuse in the right atrium (RA) and RV of patients with Ebstein’s anomaly as well as quantifying it (with pre- and post-contrast T1 mapping), which is related with disease severity and prognosis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%